The Accident Externality from Trucking - Lucija Muehlenbachs; Stefan Staubli; Ziyan Chu (Institute of Labor Economics (IZA), 2017)
The presence of a heavy truck on the road can impose an externality if accidents occur that would not have otherwise. We find each additional truck on the road increases the risk of a truck accident – but also, at an even higher rate, the risk of a car-on-car collision. Our estimates imply two percent of all car-on-car collisions can be attributed to trucks on the road. This negative externality falls on all road users through higher car insurance premiums: one truck, driving for a year in the same zip code, increases the insurance premium of each new enrollee by 0.48/year.
Keywords: G22; H23; I18; Q58; R41; 330; hydraulic fracturing; trucking; externality; traffic fatalities